Recumbent fold and deformed cut slope in the landslide-prone region of the Niigata Prefecture, Central Japan - Nozaki, Tamotsu; Ookubo, Katsumi; Yamamoto, Toshio (Journal of Nepal Geological Society, 2000)
The proposed Joushin-etsu Expressway passes along the western margin of the Takada Plain in the Niigata Prefecture. Japan. The Expressway runs through the eastern limb of the Nanbayama Anticline, which is composed mainly of Miocene sedimentary rocks. This part of the Niigata Prefecture is one of the well-known landslide-prone regions of Japan. Numerous prehistoric rockslides were identified during the preliminary investigations. Consequently, many additional studies were conducted and monitoring networks were established during the construction of tunnels and open excavations. In order to obtain representative geotechnical data for one of the excavations, detailed geological mapping, geotechnical investigation, and monitoring of a cut slope deformation were conducted. The investigations revealed unusual geological features: a thick crush zone, interbedding of sandstone and mudstone, and a recumbent fold constituting the crest of an isolated hill. The cut slopes in the crush zone started to deform during the excavation, and continued even after the completion of the excavation. We believe that the crush zone was developed tectonically, and the recumbent fold was formed as a result of the stress release induced by rapid erosion and gravity.